Analisis Kebijakan Pemerintah tentang Guru dan Dosen :Kajian Perbandingan antar Negara - Hermanto, Edi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this writing is to find out an analysis of government policies regarding teachers and lecturers: a comparative study between countries. This paper uses the library research method. The results of the research show that: 1) Law No. 14 of 2005 concerning Teachers and Lecturers has an impact on teachers, 2) Based on Article 8 it states that: